Why the personal remained political: comparing second and third wave perspectives on everyday feminism. (2nd November 2017) - Schuster, Julia
Abstract: Everyday feminist practices are located in the personal lives of feminists, therefore, third wave feminists frequently use the slogan the personal is political to emphasise the political value of such practices. Often, second wave feminists do not agree with this interpretation of the famous feminist catchphrase, which initially meant to call for collective political responses to personal experiences of gender inequalities. This article investigates this dispute that is symbolic of the broader relationship between second and third wave feminism. It compares both perspectives on everyday feminism by relating arguments for and against the political value of everyday feminism to empirical findings of a qualitative study. Based on 40 interviews with second and third wave feminists in New Zealand, I argue that the dispute is based on a number of misunderstandings between the opposing perspectives. Disentangling those misunderstandings, I conclude that although everyday feminism as a manifestation of 'the personal' works towards 'small' political aims, it is a political practice.